People, Land and Poppy: the Political Ecology of Opium and the Historical Impact of Alternative Development in Northwest Thailand - Anderson, Bobby (Forestry Faculty, Universitas Hasanuddin, 2017)
Thailand?s near-total elimination of opium poppy cultivation is attributed to ?alternative development? programming, which replaces illicit crops with licit ones. However, opium poppy cultivation was not drastically reduced because substitute crops earned the same income as opium: nothing can equal the price of opium to smallholder farmers, especially those without land tenure. Thailand?s reduction in poppy cultivation was achieved by the increased presence and surveillance capability of state security actors, who, year by year, were able to locate and destroy fields, and arrest cultivators, with increasing accuracy. This coercion was also accompanied by benefits to cultivators, including the provision of health and education services and the extension of roads; both stick and carrot constituted the encroachment of the Thai state. The provision of citizenship to hill tribe members also gave them a vested interest in the state, through their ability to hold land, access health care, education and work opportunities, amongst others. These initiatives did not occur without costs to hill tribe cultures for whom a symbiotic relationship with the land was and remains disrupted. These findings indicate that alternative development programming unlinked to broader state-building initiatives in Afghanistan, Myanmar and other opium poppy-producing areas will fail, because short-term, high-yield, high value, imperishable opium will remain the most logical choice for poor farmers, especially given the lack of a farmer?s vested interest in the state which compels them to reduce their income whilst offering them no other protections or services.